Methodological challenges of investigating in-tellectual cooperation, relational expertise, and transformative agency - Ines Langemeyer (Nordic Journal of Vocational Education and Training, 2017)
Methodological issues arise with the research of societal practices of 'knowing'. This object of study is understood as concrete human activity that always integrates mental, communicative and practical behaviour in interaction and cooperation with others. Especially with regard to contemporary forms of labour in the high-tech-world, this issue has become a salient task. As it is explained, it implies investigation of people communicating and reasoning while developing concrete forms of activity. In particular, the methodological issues concern the social and psychodynamic quality of this practice. Within the tradition of cultural-historical research and activity theory, mile-stones of this matter have already been reached. Cultural-historical concepts like the 'motive' of an activity as well as the 'emotions' that bias the 'experience' of 'transformative engagements' with the world show that their theoretical and methodological understanding are adept to approach the dialectics between the social and the individual quality of practice and agency in general, but also with regard to contemporary challenges of intellectualized cooperation in particular. 'Double stimulation', a concept coined by Vygotsky, is relevant in this context as well. However, the paper discusses critically whether it fits with the system theoretical understanding of activities and transformative agency as it can be found in Engeström's writings. Finally, the core requirements for a VET-research methodology for intellectualized collaboration are resumed.